Forefoot running requires shorter gastrocnemius fascicle length than rearfoot running - Suzuki, T.; Ogane, R.; Yaeshima, K.; Kinugasa, R. (Journal of Sports Sciences, 2019)
This study aimed to investigate the influence of foot strike patterns on the behaviour of the triceps surae muscle-tendon unit, including the Achilles tendon whose length nearly corresponds to force of the triceps surae, and the medial gastrocnemius muscle (MG) during running. Seven male volunteers ran with forefoot and rearfoot strikes at 10, 14 and 18 km h-1 on a treadmill. The MG fascicle length was measured using ultrasonography. The in vivo length of the curved Achilles tendon was quantified by combining ultrasonography with optical motion capture of reflective markers on the right lower limb and an ultrasound probe. The forefoot strike resulted in a significantly shorter MG fascicle length at the initial contact, at Achilles tendon peak elongation, and at toe-off, than the rearfoot strike. The Achilles tendon length at initial contact was greater during the forefoot strike than during the rearfoot strike at 18 km h-1, while its peak elongation was not significantly different during forefoot and rearfoot running. These results indicate that the MG, with a shorter length during forefoot running, manages to address demands for a similar peak force of the triceps surae than during rearfoot running.